Achievement on Unwrapping High Cycle Density of Noisy Phase Maps for Digital Holographic Microscopy. Issue 5 (6th April 2018) - Wang, Mingqing; Li, Fang; Zheng, Ming; Lu, Wei; Zhao, Sufen; Yu, Qingnan; Jia, Yan; Wu, Jian
Abstract: Phase unwrapping has been an important way to construct a 3‐dimensional image of the object in digital holographic microscopy. However, there is still a huge challenge currently on this technique at present, as it is still difficult to perfectly retrieve high wrapping density of phase maps which include different types of noise. This is because many details of high wrapping density of phase maps are buried in noise so that it is difficult to reconstruct them in digital holography. In order to solve this problem, a novel solution called I‐PUROR method is presented in this paper. In comparison to previous techniques, not only can the I‐PUROR algorithm effectively overcome the noise influence, but also reconstruct phase details very well in the phase unwrapping process. The experimental evaluation is fully consistent with theoretical analysis. It proves the validity of this new method. Abstract : In digital holographic microscopy, various types of noise can lead to severe image distortion from phase unwrapping, especially for high wrapping density of phase maps. The proposed I‐PUROR method in this paper demonstrates a powerful capacity of avoiding noise‐induced image distortion and preserving the phase details in phase unwrapping.